The Effect Of Job Stress And Turnover Intention On Auditor Dysfunctional Behavior With Locus Of Control As A Moderating Variable - Reina Savitri; Luqman Hakim (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research aims to examine the influence of Job Stress and Turnover Intention on Auditor Dysfunctional Behavior with Locus of Control as a Moderating Variable. The research method used is a quantitative method using primary data obtained through distributing questionnaires to respondents, namely External Auditors working at Public Accounting Firms (KAP) in the South Jakarta area. This research data test was processed using SmartPLS version 4.1.The results of this research indicate that Job Stress has a positive and significant effect on Auditor Dysfunctional Behavior, Turnover Intention has a positive and significant effect on Auditor Dysfunctional Behavior, Locus of Control has a positive and significant effect on Auditor Dysfunctional Behavior, Locus of Control is unable to moderate the effect of Job Stress on Auditor Dysfunctional Behavior, and Locus of Control is able to moderate the effect of Turnover Intention on Auditor Dysfunctional Behavior.